Evaluating the Performance of Ulee Lheue Ferry Port Facilities and Services in Banda Aceh City using the Importance Performance Analysis Method - Nurul Najwan; Renni Anggraini; Alfa Taras Bulba (Media Komunikasi Teknik Sipil, 2024)
The Ulee Lheue Ferry Port connects Banda Aceh City to Sabang City. Passenger services at the port are expected to meet the established service standards to enhance Sabang City tourism and mobility for local residents. The purpose of this study is to evaluate the performance of facilities and services at the Ulee Lheue Ferry Port based on passenger assessment. This study employs a quantitative descriptive method, with a questionnaire instrument delivered to 400 respondents using simple random sampling. Respondents should meet the following criteria: must have used port facilities and services in 2023; be over 22 years old; and have a job and income. The Importance Performance Analysis (IPA) method was used to analyse the data. By referring to the service quality (servqual) aspect, 46 indicators are utilized to measure the level of performance and its importance. The findings revealed, only 9 indicators were included in the highest priority (quadrant A), implying low performance but essential problems. Those indicators are health facilities, security facilities, bathroom conditions, service information, officers' concern, officers' responses, officers' reactions to passengers’ problems, officers' friendliness, and officers' service equality. In conclusion, this study suggests that port management and local government should improve facilities and services so that passenger service standards at Ulee Lheue Port would be significantly better.